Immigrant Adjustment in France and Impacts on the Natives - Amelie F. Constant (Institute for the Study of Labor (IZA), 2003)
The purpose of this paper is to study the immigrant performance in France and the impacts on the natives by drawing on research findings from the existing academic literature on the economics of French migration. The research questions are: how do immigrants fare with respect to wages, employment, and occupational choices; are immigrants in competition with the natives, and do they harm or improve the labour market situation of natives; does the presence of immigrants alter the internal migration flows of natives; and what is the role of the business cycle and natives? sentiments on the immigrant flows? The studies reviewed showed that while some immigrant groups are faring well, assimilation and intergenerational mobility has not taken place to a full extent. Overall, immigrants hardly affect the wages and employment levels of natives, and there are no significant displacement effects. However, the social and cultural distance between immigrants and natives is crucial in natives? sentiments. Moreover, business cycles and labour market conditions play a significant role on migration. In France of 2000, there remains a significant gap between policy goals and outcomes, indicating that integration through cultural and political venues alone is not enough but should be combined with a systematic treatment of the needs of the labour market. Lastly, there is substantial need for further studies on immigrants in France.
Keywords: J62; J24; J31; J61; F22; J18; 330; international migration; human capital; occupational choice; earnings assimilation; immigrant workers; intergenerational mobility; natives; Migranten; Soziale Integration; Arbeitsmarkt; Lohn; Ethnische Diskriminierung; Konjunktur; Schätzung; Frankreich